2000
DOI: 10.1145/335191.335426
|View full text |Cite
|
Sign up to set email alerts
|

A data model and data structures for moving objects databases

Abstract: We consider spatio-temporal databases supporting spatial objects with continuously changing position and extent, termed moving objects databases . We formally define a data model for such databases that includes complex evolving spatial structures such as line networks or multi-component regions with holes. The data model is given as a collection of data types and operations which can be plugged as attribute types into any DBMS data model (e.g. relational, or object-oriented) to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
198
0
2

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(200 citation statements)
references
References 10 publications
0
198
0
2
Order By: Relevance
“…In the proposed approach [16], some data types, namely Integer, Boolean, Spatial, can be transformed in a temporal data type. Such an abstract model has been then transformed in a discrete model [14], closer to the implementation but more restricted with respect to the abstract model. The discrete model represents the object values that have a temporal dimension through the use of snapshots.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the proposed approach [16], some data types, namely Integer, Boolean, Spatial, can be transformed in a temporal data type. Such an abstract model has been then transformed in a discrete model [14], closer to the implementation but more restricted with respect to the abstract model. The discrete model represents the object values that have a temporal dimension through the use of snapshots.…”
Section: Related Workmentioning
confidence: 99%
“…This method is thus referred to as sliced representation. As part of their work, Guting et al [14] have shown how the sliced representation can be mapped onto relational data structures such as records and arrays. However, they do not have specifically addressed how to map their abstract model onto the SQL3 standard.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these time series data usually do not involve spatial information. Although there has been some work on spatial-temporal mining [11,5] that considers both temporal and spatial aspects of information, they mainly focus on the models and structures for indexing the moving objects.…”
Section: Related Workmentioning
confidence: 99%
“…3G cell-phone or PDA enhanced by the presence of a GPS receiver), receiving hints of information, commercial spots etc. Researchers [1], [2], [3], [4], motivated from such kind of application scenarios have tried to model spatio-temporal databases using this concept of moving objects and integrate them into any extensible DBMS. On the other hand, commercial relational or object-relational database systems offer limited capability of handling this kind of non-traditional data (object trajectories, in time and space).…”
Section: Introductionmentioning
confidence: 99%